ANALISIS TENTANG MANFAAT KEIKUTSERTAAN MAHASISWA DALAM ORGANISASI KEMAHASISWAAN (STUDI PENGURUS BEM UR PERIODE 2014-2015) - Erlinda, Sri; ', Walimah; ', Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was motivated by the influence of student organizations in shaping the character of the students as candidates for the carrier changes. So the student organization is considered appropriate measures to strengthen the soft skills and hard skills of the students to prepare lunch later in the day. Therefore, the authors take the title of the study